Individual heterogeneity in life‐history trade‐offs with age at first reproduction in capital breeding elephant seals. Issue 4 (2nd July 2019) - Oosthuizen, W. Chris; Postma, Martin; Altwegg, Res; Nevoux, Marie; Pradel, Roger; Bester, Marthán N.; de Bruyn, P. J. Nico
Abstract: Recruitment age plays a key role in life‐history evolution. Because individuals allocate limited resources among competing life‐history functions, theory predicts trade‐offs between current reproduction and future growth, survival and/or reproduction. Reproductive costs tend to vary with recruitment age, but may also be overridden by fixed individual differences leading to persistent demographic heterogeneity and positive covariation among demographic traits at the population level. We tested for evidence of intra‐ and inter‐generational trade‐offs and individual heterogeneity relating to age at first reproduction using three decades of detailed individual life‐history data of 6, 439 capital breeding female southern elephant seals. Contrary to the predictions from trade‐off hypotheses, we found that recruitment at an early age was associated with higher population level survival and subsequent breeding probabilities. Nonetheless, a survival cost of first reproduction was evident at the population level, as first‐time breeders always had lower survival probabilities than prebreeders and experienced breeders of the same age. However, models accounting for hidden persistent demographic heterogeneity revealed that the trade‐off between first reproduction and survival was only expressed in "low quality" individuals, comprising 35% of the population. The short‐term somatic costs associated with breeding at an early age had no effect on the ability of females to allocate resources to offspring in the next breeding season. Our results provide strong evidence for individual heterogeneity in the life‐history trajectories of female elephant seals. By explicitly modeling hidden persistent demographic heterogeneity we show that individual heterogeneity governs the expression of trade‐offs with first reproduction in elephant seals. Abstract : We tested for evidence of intra‐ and inter‐generational trade‐offs and individual heterogeneity relating to age at first reproduction in elephant seals. Models accounting for demographic heterogeneity revealed that the trade‐off between first reproduction and survival was only expressed in "low quality" individuals. Our results provide strong evidence that individual heterogeneity governs the expression of trade‐offs with first reproduction in elephant seals.